WEWENANG INSPEKTORAT PENGAWASAN DAERAH POLDA DALAM PENCEGAHAN TINDAK PIDANA KORUPSI DI KEPOLISIAN DAERAH SULAWESI TENGAH - Nurlaelah, Nurlaelah (Universitas Tadulako, 2020)
How is the action of immigration toward the wrong offender using the residence permit for foreign people in the area of Imigration Office Class IA Palu. The purpose of reseach to know an of thed to analyze the supervision of residence permit for foreign people in the area of Imigration Office Class IA Palu. To know and to analyze the action of immigration toward the wrong offender using the residence permit for foreign people in the area of Imigration Office class IA Palu. The result of the research showed that the supervision implementation of residence permit for foreign people in the area of immigration office class I A Palu has been done of legal regulation. The supervision of resident permit for foreign people is done in administrative way since the foreign people for the Visa to visit and come to Indonesia through international airport and field supervision to evaluate the valid residence permit of the foreign people. The action administrative immigration is appropriate to be used, because tells act is more affectife than projustitia action incase of an other problem, it will projustitia action.